Drivers and Implications of Combined Investment in Renewables and Energy Storage in the Residential Sector - Cho; Kim,Youngsoo; Murali,Karthik; Yavuz,Mesut (Decision Sciences, 2023)
Residential consumers are increasingly combining renewables with energy storage systems. However, changes in policies and support for these technologies may impact their adoption and the outlook for the energy industry. In this paper, we consider a grid-connected household's problem of determining the optimal capacities of these two technologies as well as the battery operating policy that minimizes its electricity costs when faced with time-of-use electricity prices and sellback credits. We identify the impact of household characteristics, technological progress, and electricity pricing policies on the levels of investment in these two technologies. Furthermore, we supplement our analytical results with a case study of two U.S. cities and identify policy guidelines for the design of a technology subsidy program aimed at stimulating the adoption of these technologies and the ensuing implications for residential customers, the environment, and grid reliability. Our paper has implications for several stakeholders in practice on (i) how the adoption of renewables is affected by energy storage (and vice versa) and (ii) how electricity pricing, technological progress, and subsidy policies can shape the adoption of both technologies.
Keywords: Supply Chain